New melanocortin-like peptide of E. coli can suppress inflammation via the mammalian melanocortin-1 receptor (MC1R): possible endocrine-like function for microbes of the gut. (December 2017) - Qiang, Xiaoling; Liotta, Anthony; Shiloach, Joseph; Gutierrez, J.; Wang, Haichao; Ochani, Mahendar; Ochani, Kanta; Yang, Huan; Rabin, Aviva; LeRoith, Derek; Lesniak, Maxine; Böhm, Markus; et al.
Abstract E. coli releases a 33 amino acid peptide melanocortin-like peptide ofE. coli (MECO-1) that is identical to the C-terminus of theE. coli elongation factor-G (EF-G) and has interesting similarities to two prominent mammalian melanocortin hormones, alpha-melanocyte-stimulating hormone (alpha-MSH) and adrenocorticotropin (ACTH). Note that MECO-1 lacks HFRW, the common pharmacophore of the known mammalian melanocortin peptides. MECO-1 and the two hormones were equally effective in severely blunting release of cytokines (HMGB1 and TNF) from macrophage-like cells in response to (i) endotoxin (lipopolysaccharide) or (ii) pro-inflammatory cytokine HMGB-1. The in vitro anti-inflammatoty effects of MECO-1 and of alpha-MSH were abrogated by (i) antibody against melanocortin-1 receptor (MC1R) and by (ii) agouti, an endogenous inverse agonist of MC1R. In vivo MECO-1 was even more potent than alpha-MSH in rescuing mice from death due to (i) lethal doses of LPS endotoxin or (ii) cecal ligation and puncture, models of sterile and infectious sepsis, respectively. Gut bacteria: Helping out with hormones? A molecule released by the common bacteriumE. coli may act like a hormone on cells in the gut, with beneficial anti-inflammatory effects. The molecule is a short protein fragment known as a peptide. Its hormone-like activity on cultured mammalian cells was discovered by an international team of researchers led by Jesse Roth at the Feinstein Institute for Medical Research in Manhasset, USA. The peptide shares structural similarities with two known mammalian hormones and binds to an identified hormone receptor molecule. In some circumstances, it was shown to save mice from death by suppressing damaging inflammation. This discovery could broaden our understanding of the beneficial effects of gut bacteria. If applicable in humans it could reveal another link in our subtle relationship with bacteria, and may lead to uses in preventive and therapeutic medicine.